Evaluation of Instagram’s popularity: Brand cue and message appeal as explanatory variables - Anggraini, Putri; Gunarto, Muji (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
The internet’s ascent has transformed digital marketing, with social media platforms like Instagram becoming essential tools. The “Instagrammable” trend has gained traction in the food industry, using visual appeal to drive business success and expand markets. This research investigates the factors influencing Instagram’s popularity metrics in the food sector, focusing on South Sumatra. A survey of 250 Instagram users was conducted using accidental sampling. The study assessed various factors on a Likert scale from 1 (strongly disagree) to 7 (strongly agree). The findings revealed that brand cue positively impacts selling strategy and information search. Additionally, message appeal positively influences selling strategy and information search but negatively correlates with the popularity of social media messages, suggesting that specific appeals might hinder social media popularity. Conversely, selling strategy and information search positively affect the popularity of social media messages, highlighting the importance of engaging consumers and providing informative content for brand popularity on social platforms. While brand cues do not directly influence the popularity of social media messages, message appeal and brand cues are crucial in shaping consumer interactions on social media. These results offer practical insights into utilizing brand cues and message appeal to cultivate consumer relationships, differentiate brands, and influence purchasing behavior through social media. The study provides valuable guidance for businesses navigating the complex world of social media marketing, emphasizing the importance of tailored messaging and brand presence in driving consumer engagement and brand perception within the competitive food industry.